Assessing the efficiency of a mobile application in reading hematocrit compared to the manual method and automated blood cell analyzer - Jitjan, Geerati; Treebuphachatsakul, Wanvisa; Apiratmateekul, Napaporn; Chaisomboon, Chaiwat; Waranusast, Rattapoom; Kongros, Kunchit (Health Science, Science and Technology Reviews, 2025)
The measurement of packed red cell volume, or hematocrit, remains a widely used method for screening anemia and monitoring treatment across various patient groups. The standard method for hematocrit measurement is the microhematocrit technique, which is simple, convenient, low-cost, and requires only a small blood sample. However, this method has limitations, particularly when the operator lacks proficiency in reading the hematocrit level especially in individuals with visual impairments. Moreover, in high-volume testing scenarios, manual reading and reporting errors may occur. Recognizing these challenges, the researchers developed a mobile phone application to assist in reading hematocrit values. The study evaluated the application’s accuracy using blood samples adjusted to hematocrit levels in three ranges: 20–25%, 40–45%, and 60–65%. The coefficient of variation (%CV) for the application readings in these three ranges was found to be 0.9, 1.3, and 0.8, respectively. The accuracy values were -2.4%, -2.1%, and -2.2%, respectively. A total of 171 samples were tested and compared using the microhematocrit method, an automated hematology analyzer, and the mobile application (in both automatic and manual modes). The correlation coefficients for these comparisons were 0.990, 0.990, 0.974, 0.973, 0.992, and 0.981, indicating a high level of correlation. The intraclass correlation coefficients (ICC) further confirmed high consistency, with values of 0.995, 0.995, 0.987, 0.986, 0.996, and 0.990 (P < 0.001). Additionally, the application was capable of measuring hematocrit in turbid samples and those with red cell hemolysis up to grade 4+. User satisfaction among those who tested the application was rated as good (mean score of 4.43 ± 0.64). In conclusion, this mobile application can serve as an effective alternative to standard microhematocrit methods and automated hematology analyzers, particularly in settings with limited laboratory equipment.